2004
DOI: 10.1128/aem.70.10.6123-6130.2004
|View full text |Cite
|
Sign up to set email alerts
|

Helix 4 Mutants of the Bacillus thuringiensis Insecticidal Toxin Cry1Aa Display Altered Pore-Forming Abilities

Abstract: The role played by ␣-helix 4 of the Bacillus thuringiensis toxin Cry1Aa in pore formation was investigated by individually replacing each of its charged residues with either a neutral or an oppositely charged amino acid by using site-directed mutagenesis. The majority of the resulting mutant proteins were considerably less toxic to Manduca sexta larvae than Cry1Aa. Most mutants also had a considerably reduced ability to form pores in midgut brush border membrane vesicles isolated from this insect, with the not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
63
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(69 citation statements)
references
References 47 publications
6
63
0
Order By: Relevance
“…For example, (i) Cry toxin can insert into bilayer lipid rafts and BBMV irrespective of toxin receptors, 20 (ii) toxin oligomer complexes can form in BBMV prepared from insects that are not susceptible to Cry toxin 29,47 and (iii) Cry toxin mutants that are not insecticidal induce changes in membrane permeability similar to wild-type toxin. 27,28 In the present study, we used an H5 insect cell-based system that allowed us to simultaneously correlate toxinreceptor and toxin-membrane interactions with cellular responses associated with cytotoxicity. An important distinction of this system is the ability to examine incorporation of Cry1Ab toxin into cell membrane and to monitor the interaction of the toxin with BT-R 1 in live insect cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, (i) Cry toxin can insert into bilayer lipid rafts and BBMV irrespective of toxin receptors, 20 (ii) toxin oligomer complexes can form in BBMV prepared from insects that are not susceptible to Cry toxin 29,47 and (iii) Cry toxin mutants that are not insecticidal induce changes in membrane permeability similar to wild-type toxin. 27,28 In the present study, we used an H5 insect cell-based system that allowed us to simultaneously correlate toxinreceptor and toxin-membrane interactions with cellular responses associated with cytotoxicity. An important distinction of this system is the ability to examine incorporation of Cry1Ab toxin into cell membrane and to monitor the interaction of the toxin with BT-R 1 in live insect cells.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of mutated Cry toxin proteins have shown that neither the toxin oligomer complex nor commensurate changes in membrane vesicle permeability correlate directly with toxicity. [26][27][28][29] Furthermore, Cry toxin proteins can interact with lipid bilayer rafts and BBMV in the absence of a cadherin receptor, which determines specific insecticidal activity of Cry toxins.…”
Section: Introductionmentioning
confidence: 99%
“…Changes in membrane permeability were correlated with the incorporation of Cry toxin oligomers into lipid bilayer rafts and brush border membrane vesicles (8,16). However, studies of mutated Cry toxin proteins have shown that neither the toxin oligomer complex nor commensurate changes in membrane vesicle permeability correlate directly with toxicity (17)(18)(19). Interestingly, Cry toxin oligomers also are incorporated into the cell membrane of nonsusceptible cabbage looper cells and are carried by the cells for several generations with no adverse effect (14).…”
mentioning
confidence: 99%
“…There is also evidence that other domains of the protein are able to insert into membrane [16], and that several mutations in the domain I (α-helices 3 and 4) affect oligomer formation [18][19][20]. Several disulfide-bridge mutations generated by protein engineering which are related to the membrane partitioning mechanisms of Cry toxins are reviewed in [21].…”
Section: Introductionmentioning
confidence: 99%